Case Analysis of Turbulence From High-Resolution Sounding Data in Northwest China - Qin, Zilin; Sheng, Zheng; He, Yang; Feng, Yutao (Frontiers in Environmental Science, 2022)
This study calculated the Thorpe scale, thickness of turbulent layer, turbulent kinetic energy dissipation rate and turbulent diffusion coefficient based on the Thorpe method using a set of near-space high-resolution radiosonde data in northwest China, and a case study was conducted to analyze the large-scale turbulent layer in the middle stratosphere. The results showed that the most turbulent layers exist near the middle and upper troposphere to tropopause region, accounting for 44.0% of the total turbulence, and the largest Thorpe scale and thickness of turbulent layer also appear in this altitude range. In addition, affected by the large-scale turbulence near the tropopause, the calculated turbulent energy dissipation rate and diffusion coefficient also have maximum values at this altitude, which are 0.003m^2 s^(-3)and 6.94m^2 s^(-1), respectively. By analyzing the weather conditions, it is found that there is an obvious correlation between precipitation and large-scale turbulence in stratosphere. When the precipitation comes, the corresponding two sets of radiosondes detected larger-scale turbulence layers in the middle stratosphere.